ApoE polymorphisms in narcolepsy - Kasten Meike; Wieczorek Stefan; Dahmen Norbert; Gencik Martin; Gencikova Alexandra; Epplen Jorg T (BMC Medical Genetics, 2001)
Summary Background Narcolepsy is a common neuropsychiatric disorder characterized by increased daytime sleepiness, cataplexy and hypnagogic hallucinations. Deficiency of the hypocretin neurotransmitter system was shown to be involved in the pathogenesis of narcolepsy in animals and men. There are several hints that neurodegeneration of hypocretin producing neurons in the hypothalamus is the pathological correlate of narcolepsy. The ApoE4 allele is a major contributing factor to early-onset neuronal degeneration in Alzheimer disease and other neurodegenerative diseases as well. Methods To clarify whether the ApoE4 phenotype predisposes to narcolepsy or associates with an earlier disease onset, we have genotyped the ApoE gene in 103 patients with narcolepsy and 101 healthy controls. Results The frequency of the E4 allele of the ApoE gene was 11% in the patient and 15% in the control groups. Furthermore, the mean age of onset did not differ between the ApoE4+ and ApoE4- patient groups. Conclusion Our results exclude the ApoE4 allele as a major risk factor for narcolepsy.